2013
DOI: 10.5370/jeet.2013.8.6.1451
|View full text |Cite
|
Sign up to set email alerts
|

Robust Zero Power Levitation Control of Quadruple Hybrid EMS System

Abstract: -This paper presents the improved zero power levitation control algorithm for a quadruple hybrid EMS (Electromagnetic Suspension) system. Quadruple hybrid EMS system is a united form of four hybrid EMS systems one on each corner coupled with a metal plate. Technical issue in controlling a quadruple hybrid EMS system is the permanent magnet's equilibrium point deviation caused by design tolerance which eventually leads to a limited zero power levitation control that only satisfies the zero power levitation in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…where k c1 and k c2 are the coefficient of the current loop. The time constant is then changed to be T ′ = L 0 ∕(R + k c1 k c2 ), the time delay of the electromagnet windings is thus reduced dramatically if k c1 k c2 >> R. By combining (5) and (6), the proportional value between the winding current value i and controller output value u in steady state can be obtained as:…”
Section: Controller Design 221 Current Loop Designmentioning
confidence: 99%
See 1 more Smart Citation
“…where k c1 and k c2 are the coefficient of the current loop. The time constant is then changed to be T ′ = L 0 ∕(R + k c1 k c2 ), the time delay of the electromagnet windings is thus reduced dramatically if k c1 k c2 >> R. By combining (5) and (6), the proportional value between the winding current value i and controller output value u in steady state can be obtained as:…”
Section: Controller Design 221 Current Loop Designmentioning
confidence: 99%
“…To further optimize the energy consumption of the maglev train, a new kind of permanent magnet electro-magnetic suspension (PEMS) type maglev is proposed. In the PEMS maglev, a permanent magnet is added inside the core of the electromagnet to share part of the load [5]. The energy consumed is reduced and the overheating problem is solved [6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and et al [6] focused on the optimal structural design of the PEMS magnet and proposed optimized parameters with better carrying capability and lower suspension power loss. Cho and et al [16] reported a successful quadruple PEMS system with the improved zero-power control algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some researches about PEMS maglev these years. Su-Yeon Cho et al utilized zero-power control for a quadruple PEMS system [9], in this experiment setup, four PEMS systems are bounded on each corner of a square metal plate, the structural coupling influences the whole system's performance. In [10], an optimizing method was adopted on permanent magnet parameters to minimize the power loss while maximize the carrying capacity at the same time under system constrains.…”
Section: Introductionmentioning
confidence: 99%